Simulasi Tegangan pada Rangka Sepeda Motor ESAF Menggunakan Metode Finite Element Analysis - Syahrial Garindra; Rachmat Dwi Sampurno; Sailon Sailon (Politeknik Kampar, 2024)
The research evaluates the durability of the ESAF frame using finite element analysis (FEA). The simulation examines von Mises stress, displacement, and safety factor under load variations of 300 kg, 350 kg, and 400 kg. Results show von Mises stress values of 305.5 MPa, 356.3 MPa, and 406.8 MPa, which are within the tensile strength range of high-strength low alloy steels (HSLA) at 750–1500 MPa, indicating structural safety. Displacement values are 0.03131 mm, 0.03652 mm, and 0.04174 mm, with minimal deformation demonstrating stability. Safety factor values are 5.0, 4.2, and 3.75, exceeding the safe limits of 3.0 for dynamic and 2.0 for static loads based on journal references. These findings confirm that the ESAF frame is theoretically safe for the given load conditions.